Benefit requirements for substance use disorder treatment in state health insurance exchanges. (4th July 2018) - Tran Smith, Bikki; Seaton, Kathleen; Andrews, Christina; Grogan, Colleen M.; Abraham, Amanda; Pollack, Harold; Friedmann, Peter; Humphreys, Keith
ABSTRACT: Background : Established in 2014, state health insurance exchanges have greatly expanded substance use disorder (SUD) treatment coverage in the United States as qualified health plans (QHPs) within the exchanges are required to conform to parity provisions laid out by the Affordable Care Act and the Mental Health Parity and Addiction Equity Act (MHPAEA). Coverage improvements, however, have not been even as states have wide discretion over how they meet these regulations. Objective : How states regulate SUD treatment benefits offered by QHPs has implications for the accessibility and quality of care. In this study, we assessed the extent to which state insurance departments regulate the types of SUD services and medications plans must provide, as well as their use of utilization controls. Methods : Data were collected as part of the National Drug Abuse Treatment System Survey, a nationally-representative, longitudinal study of substance use disorder treatment. Data were obtained from state Departments of Insurance via a 15-minute internet-based survey. Results : States varied widely in regulations on QHPs' administration of SUD treatment benefits. Some states required plans to cover all 11 SUD treatment services and medications we assessed in the study, whereas others did not require plans to cover anything at all. Nearly all states allowed the plans to employ utilization controls, but reported little guidance regarding how they should be used. Conclusion : Although some states have taken full advantage of the health insurance exchanges to increase access to SUD treatment, others seem to have done the bare minimum required by the ACA. By not requiring coverage for the entire SUD continuum of care, states are hindering client access to appropriate types of care necessary for recovery.